Irrational use of antibiotics and clinical outcomes in children with pneumonia - Yusuf Yusuf; Indah Kartika Murni; Amalia Setyati (Indonesian Pediatric Society, 2017)
Background Pneumonia is a major cause of morbidity and mortality in children under five. Antibiotic treatment must be started immediately in children with pneumonia. The irrational use of antibiotics may increase morbidity and mortality in children with pneumonia.Obejctive To determine the prevalence of the irrational use of antibiotics and clinical outcomes in children with pneumonia.Methods We conducted a cross-sectional study in children with pneumonia who were admitted to the Pediatric Ward or PICU at Dr. Sardjito Hospital, Yogyakarta, from December 2010 to February 2013. Data were obtained from subjects’ medical records. Children with malnutrition, congenital heart defects, sepsis, shock, central nervous system disorders, syndromes, or other concomitant infections were excluded.Results Of 46 children who fulfilled the inclusion criteria, 13 (28.3%) used antibiotics irrationally and 7 (15.2%) died. Most subjects were aged less than 1 year (25 subjects, 54.3%) and 1 - < 5 years (18 subjects, 39.1%). The female to male ratio was 1:1. Most cases were referred from other hospitals (23 subjects, 50%). Twenty-eight (60.9%) subjects stayed in hospital > 7 days. Ampicillin was the most common first-line, empirical antibiotic used (32 subjects, 69.6%). Blood cultures were obtained in 20 (43.5%) patients, yielding no growth in 16 subjects, coagulase-negative staphylococci (CONS) in 3 subjects, and Pseudomonas aeruginosa in 1 subject. The irrational use of antibiotics was significantly associated with mortality in a univariate analysis [PR 6.35; (95%CI 1.40 to 28.69); P=0.006]. Conclusion The irrational use of antibiotics is common among children with pneumonia and is significantly associated with mortality.